Beyond pre-loading: Understanding the associations between pre-, side- and back-loading drinking behavior and risky drinking. (February 2016) - O'Rourke, Sean; Ferris, Jason; Devaney, Madonna
Abstract: This study examined the interaction between pre-, side- and back-loading drinking behaviors and their relationship to risky drinking, modeling to account for demographic characteristics. The study was based on an online non-probability panel survey of Victorian adults (18 +) who purchased packaged liquor for off premises consumption in the previous 12 months. Initially, 2545 participants entered the study, with 536 screened out, leaving a sample of 2008 respondents. While pre-loading was the most commonly reported loading behavior, back-loading and side-loading were reported almost as frequently. We found a clear association between loading and risky drinking behavior. Respondents who reported engaging in all loading behaviors were more likely to report regular very risky drinking. Age and sex were significant factors influencing the relationship between loading types and risky drinking behavior; income, marital status, and the interaction between sex and age were not significant factors. We show a broad range of loading behaviors associated with increased levels of risky drinking. Future research should seek to investigate these loading behaviors among a general population sample. Highlights: 42.1% of the sample reported at least one 'loading' behavior. Those reporting loading were on average 12 years younger than those who did not. Risky drinking was strongly associated with having pre, side or back loaded. Loading behavior varied by age and gender.